Synthesis of Polymerization of New Derivative of 2-Decanoic Acid Extracted from Coriander Seed - Fatimah Ali Hussein (Journal of Global Pharma Technology, 2019)
This work, includes  preparation of the derivative of decanoic acid  was extracted  from conriander seeds by fractional distillation for four hours, then reacted with one groups of amin of  thio urea  the2nd group  amin in thioureia was  reacted  with maleic anhydride a  different drugs was used to obtain  novel  derivatives.  The compounds  written off as  by using some spectroscopic methods, H1NMR and  FT-IR used to characterization the derivatives, control drug release was studying of some derivatives, biological activity against bacterial was studying and thermal stability of the derivatives.Keywords: Decanoic acid, Conriander seeds, FT-IR, H1NMR